Students’ Perception of Learning English with E-Learning During Covid-19 Pandemic - Diana Merliana Rahman; Desty Febria (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2023)
This study aims to find out the perceptions and difficulties of Univesitas Internasional Batam students in learning English online using E-Learning (Learning Management System), what are the difficult factors that affect UIB students in learning using E-Learning during the Covid-19 pandemic. This research was conducted using quantitative methods. Participants in this study were Universitas Internasional Batam students totaling 100 students from the 2019-2021 batch from various majors. Data was obtained by using a questionnaire. To evaluate the data, the researcher used a Likert scale and categorizes it in the form of strongly agree, agree, disagree, and strongly disagree. The results of the perception of this study indicate that most of UIB students have a very positive perception with the use of E-Learning in online English learning during the Covid-19 pandemic, this is supported by the perception factor from question no 9 that the learning materials in UIB's E-Learning are easy accessed anywhere, the average of these questions is 3.49. However, from the results of this study, there were 5 difficulty factors that affected UIB students, namely (1) question 15: low motivation statements when studying online using E-Learning with an average data of 2.77. (2) question 12: statement of lack of understanding about E-Learning features with an average data of 2.57. (3) question 20: statement of increasing internet quota on the use of E-Learning with an average data of 2.48. (4) question 18: statement Using E-Learning to learn English during this pandemic is uncomfortable with an average of 2.29. (5) question 19: the statement that it is difficult to access the internet network at E-Learning sites with an average data rate of 2.27.